A comparison of emotional responses between personal and historical nostalgia - Marchegiani, Chris (School of Marketing, Curtin Business School, 2009)
This research examines the differences in emotional responses of 806 respondents exposed to Personal or Historical Nostalgic advertising appeals using experimental research design. Five emotions common to both conditions are revealed and significant changes in intensity of these emotions are explored. As hypothesised, emotions are significantly more intense under the Personal Nostalgic condition compared to the Historical, although not in all five emotion components. This research highlights the need to treat Nostalgia as two separate appeals and provides insight useful to practitioners about these distinct reactions. It also suggests the need for future research into Personal and Historical Nostalgia?s effects.